2002
DOI: 10.1152/ajpcell.00216.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TonEBP transcriptional activator in MDCK cells following changes in ambient tonicity

Abstract: In response to ambient hypertonicity, TonEBP (tonicity-responsive enhancer binding protein) stimulates certain genes including those encoding cytokines, transporters for organic solutes, and a molecular chaperone. TonEBP is regulated in a bidirectional manner, upregulated by an increase in ambient tonicity while downregulated by a decrease. To investigate the role of intracellular ionic strength in the activity of TonEBP, we subjected Madin-Darby canine kidney cells to a variety of conditions. Electron micropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 28 publications
0
52
1
Order By: Relevance
“…On the other hand, inhibition of Na-K-ATPase by ouabain leads to decreased activity of TonEBP/OREBP despite a marked increase in the intracellular ionic strength. It was suggested that, because isotonic swelling is known to occur under these conditions, dilution of the cytoplasmic constituents inhibits the activity of TonEBP/OREBP (36). However, the present study affords an alternative explanation as the effect of ouabain on TonEBP/ OREBP is associated with suppression of ROS formation (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…On the other hand, inhibition of Na-K-ATPase by ouabain leads to decreased activity of TonEBP/OREBP despite a marked increase in the intracellular ionic strength. It was suggested that, because isotonic swelling is known to occur under these conditions, dilution of the cytoplasmic constituents inhibits the activity of TonEBP/OREBP (36). However, the present study affords an alternative explanation as the effect of ouabain on TonEBP/ OREBP is associated with suppression of ROS formation (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Hypertonicity shrinks cells by osmosis, resulting in increased concentration of all intracellular components, including intracellular ions (36) and macromolecules (6). Decrease in cell volume (12), increase in intracellular ionic strength (36), and increased macromolecular crowding (6) are all candidates to be sensors that trigger cellular responses to hypertonicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations